Pengaruh Kecerdasan Emosional Dan Kontrol Perilaku Terhadap Minat Berkarir Menjadi Akuntan Publik: (Studi Empiris Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Jurusan Akuntansi Universitas Pattimura) - Samie Jacobs; Agustina Christina Patty (Jurnal Administrasi Terapan, 2024)
This study aims to determine empirically the influence of emotional intelligence and the influence of behavior control on career interest as a public accountant. The sample of this study was undergraduate students of the Faculty of Economics and Business, Department of Accountancy, Pattimura University batch 2018, who were still active as many as 140 respondents. The sampling technique used was non-probability sampling with the characteristic of purposive sampling. The data used are primary data collected through questionnaires to respondents. The data obtained were then analyzed using multiple linear regression analysis techniques with the help of SPSS 24 software. The results of the study proved that: (1) The level of Emotional Intelligence of the Students of the Faculty of Economics and Business, Pattimura University, Ambon greatly influenced the Career Interest of Being a Public Accountant. (2) The low behavioral control of students from the Faculty of Economics and Business, Pattimura University, Ambon, grestudy’s resultsatly affects the interest in having a career as a public accountant. (3) It shows that the higher the employment intelligence and behavioral control a person has, the higher the career interest in becoming a public accountant. Keywords: Public Accountant, Emotional Intelligence and Behavior Control